2019
DOI: 10.25008/jkiski.v4i1.255
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and General Election in Southeast Asia (Malaysia 2018 and Indonesia 2019)

Abstract: On 2018 and 2019, Malaysian and Indonesian voters set off to the polls to elect their new goverment as Pre Minister for Malaysia and President - Vice President for Indonesia. They are also elect members of the national Regions House, a kind of weak Senate, together with members of the powerful House of Representatives. In addition they will elect provincial councillors from every Provinces and also elect local councillors across local authorities. Related to this situation, discussion and prediction about who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 10 publications
0
14
0
4
Order By: Relevance
“…And the third has a form of response. So it can be concluded that political persuasive is an invitation, persuasion, seduction, with a nonviolent form that is done by political communicators to the community as a community with the aim that the community can provide support, A response, sympathy for him in terms of power in a country [13].…”
Section: Persuasive Communicationmentioning
confidence: 99%
“…And the third has a form of response. So it can be concluded that political persuasive is an invitation, persuasion, seduction, with a nonviolent form that is done by political communicators to the community as a community with the aim that the community can provide support, A response, sympathy for him in terms of power in a country [13].…”
Section: Persuasive Communicationmentioning
confidence: 99%
“…The validity of heroism in a person is influenced by ethnic stereotypes in the country, religion, routine charismatic authority, and other custom labels or schemes. The construction of an official picture of a particular politician leads to a general picture that resonates with people with certain primordialities [20]. The first indicator is supported by the existence of the capital city as a source that needs to be considered in influencing the social context which is then able to influence the social biography of a figure or politician.…”
Section: Teguh Lurungbudi Etal (Activists Communication Dynamics)mentioning
confidence: 99%
“…Therefore the district boundary needs to be shifted [2]. Whereas in Indonesia itself #2019GantiPresiden movement has become one of the references how the Internet can provide a very remarkable effect on the mass movements in the real world [3].…”
Section: Introductionmentioning
confidence: 99%